BREAST IRONING: A RAPE OF THE GIRL-CHILD’S PERSONALITY INTEGRITY AND SEXUAL AUTONOMY - Titi Christiana Falana (Universitas PGRI Madiun, 2020)
Breast ironing also known as breast flattening, has been considered as one of the most widespread and systematic violations of the universal human rights to personal integrity and sexual autonomy perpetuated against the girl child. This exhilarating practice which is typically carried out by the girl’s mother on the pretext of protecting the female child from teenage sexual harassment and rape, early pregnancy and dropping out of school is unfortunately done to protect family name. Employing the qualitative research approach and the expository analytic method, this research reveals that this practice has ensuring clinical, psychological and social consequences on the female victim. The paper considers this practice a rape based on the fact that the female victim’s consent is never sought. Natural sense of justice demands that the victim whose personality integrity and right to sexual autonomy was to be defiled and destroyed deserves to give an informed consent. Therefore, the paper concludes that this harmful practice is an abuse because it violently violates the girl child right full sexual autonomy and right to possess natural physiological endowment that adorns a woman. This paper therefore recommends that strict laws and penalties should be promulgated to totally abolish and eradicate this barbaric and horrific mutilation.